2003
DOI: 10.1162/154475203771799702
|View full text |Cite
|
Sign up to set email alerts
|

The Internet in India and China

Abstract: With our colleagues in the Mosaic group, we have done several studies of the state of the Internet in India and in China beginning in 1998. These studies were conducted using a six-dimension framework we have developed for characterizing the state of the Internet in a nation. In 1999, we published a comparison of the state of the Internet in China and India. At that time we found that China had a clear lead in each of our six dimensions. This paper updates the comparison. We compare China and India on our six … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Second, if so, could China control it (Kluver & Yang, 2005)? Similar to telecommunications, the strong determination of the government to make the internet a national priority, the Chinese ability to execute by administrative decree rather than consensus building followed by legislative and regulatory reform and the Chinese tendency to introduce internal competition were identified as the key factors to help China jump-start the internet (Press, Foster, & Goodman, 1999;Press, Foster, Wolcott, & McHenry, 2003).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Second, if so, could China control it (Kluver & Yang, 2005)? Similar to telecommunications, the strong determination of the government to make the internet a national priority, the Chinese ability to execute by administrative decree rather than consensus building followed by legislative and regulatory reform and the Chinese tendency to introduce internal competition were identified as the key factors to help China jump-start the internet (Press, Foster, & Goodman, 1999;Press, Foster, Wolcott, & McHenry, 2003).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The stakeholders involved can be categorized as regions, countries and areas (Mendoza, 2001; Norris, 2001; Simpson, Daws & Pini, 2004); communities and organizations (Johnson, 1998; Rooney, 2002); and groups of people (Millward, 2003). The dimensions can be demographical (Brinson, 2002; Losh, 2004), economic (McLaren & Zappalà, 2002), political (Hung, 2004) and cultural (Press et al, 2002). As far as demographical factors are concerned, age, gender, income, race and education are the most important ones, with younger, richer, more educated white males being more likely to use the Internet (Hargittai, 2002; Miller, 2001).…”
Section: Digital Dividementioning
confidence: 99%
“…Prior research that has studied the link between the cost of Internet access and its diffusion in several countries (e.g., China, Chile, India, South Korea) found that lower computer costs combined with lower access costs make the Internet more affordable and facilitate its growth (Hawkins, 2005;Lee et al, 2003;Press et al, 2002). Additionally, the most recent large-scale survey of 57,000 households in 2003 by the United States Department of Commerce reported that one of the reasons that households have no Internet connection is its costs.…”
Section: Hypotheses Related To Within-country Factorsmentioning
confidence: 99%